The Effect of Using on Viral Playlist at Spotify on the Students’ Listening Skill at the Tenth Grade MAN 1 Kota Kediri - Yanuar Lazuardy; Yunik Susanti; Suhartono Suhartono (Proceedings Series on Social Sciences & Humanities, 2023)
Listening is the first skill and basic ability in learning a new language that beginners have to learn. In this era, technology is getting better and students’ can easy to learning English. Researcher use the most popular music platform that can be applied in teaching listening, named Spotify. The researcher used quantitative research, and the research was conducted at MAN 1 Kota Kediri. The sample was X IPS 1 class that consists of 36 students. The students were given pre-test, treatment, and post-test. The treatment was conducted once in order to know whether is an significant effect of using on viral playlist at Spotify in teaching listening skill. The data result got from students’ score of pre-test and post-test that analyzed using t-test formula. The researcher uses SPSS version 20.0. The data result shows that t-score is higher than t-table in the level significant of 5%. The mean score of pre-test is 72,86 with the total score 2.687 and mean score of post-test is 83,92 with the total score 3.109. The result of the research shows that there is any significant effect of using the treatment, it is proven by the different score between pre-test and post-test.